PENERAPAN KURIKULUM MERDEKA DALAM MATA PELAJARAN PPKN KELAS X DI SMA NEGERI 6 KOTA TERNATE - Umasangaji, Rizal; Kamisi, Mohtar; Wicaksono, Muhammad Arif (Jurnal GeoCivic, 2025)
Based on the results of research carried out by researchers, there are still many students and teachers who are confused about the implementation of the independent curriculum regarding the implementation of the independent curriculum. One of them is in Civics subjects. Therefore, teachers must know more about the application of the independent curriculum to the learning process in schools. Teachers must also understand that assessments, teaching modules and other components in the independent curriculum and the 2013 curriculum are very different. The independent curriculum is a form of refinement of the 2013 curriculum, of course it has received a variety of responses from several teachers, students and parents. From several related parties, there are some who support it and there are also many who complain about the changes to the independent curriculum that have been implemented. Obstacles The implementation of the independent curriculum at SMA Negeri 6 Ternate City in class X PPKN subjects is still experiencing several obstacles. Especially in relation to teachers' lack of understanding. As well as students' difficulties understanding in class and still adapting.